2014
DOI: 10.1007/s11095-014-1564-3
|View full text |Cite
|
Sign up to set email alerts
|

Human ALDH1B1 Polymorphisms may Affect the Metabolism of Acetaldehyde and All-trans retinaldehyde—In Vitro Studies and Computational Modeling

Abstract: Purpose To elucidate additional substrate specificities of ALDH1B1 and determine the effect that human ALDH1B1 polymorphisms will have on substrate specificity. Methods Computational-based molecular modeling was used to predict the binding of the substrates propionaldehyde, 4-hydroxynonenal, nitroglycerin, and all-trans retinaldehyde to ALDH1B1. Based on positive in silico results, the capacity of purified human recombinant ALDH1B1 to metabolize nitroglycerin and all-trans retinaldehyde was explored. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…ALDH1B1 can regulate the expression of PI3K and AKT via the FABP5/PPARD signaling pathway, and can regulate the expression of β‐catenin, thus promoting the occurrence of colorectal cancer (Singh et al, ). The ALDH1A1 and ALDH1B1 protein sequences are 62% similar, and as both are known to catalyze the formation of RA (Jackson et al, ; Singh et al, ), it is possible that ALDH1A1 also plays a role in the regulation of the FABP5/PPARD‐PI3K/AKT‐Wnt/β‐catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1B1 can regulate the expression of PI3K and AKT via the FABP5/PPARD signaling pathway, and can regulate the expression of β‐catenin, thus promoting the occurrence of colorectal cancer (Singh et al, ). The ALDH1A1 and ALDH1B1 protein sequences are 62% similar, and as both are known to catalyze the formation of RA (Jackson et al, ; Singh et al, ), it is possible that ALDH1A1 also plays a role in the regulation of the FABP5/PPARD‐PI3K/AKT‐Wnt/β‐catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates our previous in vitro study showing that ALDH1B1 is second only to ALDH2 in oxidizing acetaldehyde, and indicates that ALDH1B1 plays a functionally significant role in acetaldehyde clearance in vivo . This finding may have clinical implications given that several functional polymorphisms of ALDH1B1 gene have been identified in the human population [8]. Alcohol hypersensitivity has been observed in carriers of the ALDH1B1*2 variant [5], which metabolizes acetaldehyde at a slower rate than wild-type ALDH1B1 [8].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this notion, human studies have identified ALDH1B1 polymorphisms to be associated with symptoms of acetaldehyde toxicity including ethanol hypersensitivity, hypertension and ethanol aversion in Caucasian populations [5, 6], where the well-studied ALDH2*2 variant is nearly absent [7]. In addition to its acetaldehyde metabolic effects, ALDH1B1 has the catalytic capacity for oxidation of retinaldehyde [8], which is supportive of ALDH1B1 playing a role in the differentiation and development of normal and cancer stem cells [9]. In this context, we have observed that ALDH1B1 is expressed specifically in the stem cell compartment in the normal colon and is drastically induced in human colon cancerous tissues [10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on its possible ability to enzymatically convert retinal to retinoic acid, ALDH1B1 is presumed to promote differentiation of stem cells ( Chute et al , 2006 ; Jackson et al , 2015 ). Indeed, a previous study reported that ALDH1B1 protein expression in human CRC was increased in line with the extent of differentiation ( Langan et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%